Study on the durability of HDPE geomembranes applied to geotechnics and the environment using laboratory aged samples and in situ exhumed samples - Lavoie, Fernando Luiz (2021)
The polymer demand for geotechnical applications has been growing. The geomembrane is a geosynthetic, manufactured, polymeric product and is often specified in environmental and hydraulic projects. Over the past forty years, millions of square meters of HDPE geomembrane have been used in different applications. One of the most important issues for HDPE geomembranes is the durability, involving very long-term property requirements. This work analyzed exhumed and laboratory aged HDPE geomembrane samples using physical and thermal analyses. The virgin samples evaluated in this research were smooth and with nominal thicknesses of 1.0 (1L sample), 1.5 (1.5L sample) and 2.0 mm (2L sample). The exhumed samples were collected in different Brazilian construction works in many geotechnical and environmental applications. The CLIQ sample was exhumed from an industrial water pond after 2.25 years of field exposure. The LTE sample was exhumed from an aeration pond by sewage treatment after 2.75 years of exposure. The LCH sample was exhumed from a municipal landfill leachate pond after 5.17 years of exposure. The MIN and MIN2 samples were exhumed from mining facilities after, respectively, 7.92 and 10.08 years of exposure. The LDO sample was exhumed from a biodegradable waste pond after 15.17 years of exposure. The CAM, CAM1 and CAM2 samples were exhumed from shrimp farming ponds, that the CAM and CAM1 samples were exhumed from the same pond, but the CAM sample was taken from the bottom liner and the CAM1 sample from the slope liner, both after 8.25 years of exposure. The CAM2 sample was taken from another shrimp farming pond after 3.0 years of field exposure. The analyzed exhumed geomembranes demonstrated several changes in their properties, including low stress crack resistance (SCR) values and low Std. OIT (oxidative-induction time), which could conduct a liner rupture in a short-term, except for the LCH sample, the thickest exhumed sample, which presented good performance in the physical properties, but some changes in thermal decomposition. For the UV fluorescent radiation, after 8760 h of exposure, the 1L sample demonstrated losses in tensile properties and a considerable antioxidant depletion, changing its performance as a liner. It was observed that the 1.5 mm-thick HDPE geomembrane had losses in SCR, high antioxidant consumption, a change in the thermal behavior before the melting point, but maintained the viscosity of the polymer and preserved the ductility. The virgin samples presented several changes in some evaluated properties after the thermal exposure (8760 h) and the synergy exposure to UV radiation (8760 h) and thermal aging (4380 h), highlighting for the MFI (melt flow index) results, which demonstrated the occurrence of cross-linking reactions for all samples. Moreover, all samples presented considerable changes in SCR behavior and high antioxidant depletion. Finally, this research evidenced the necessity to homogenise the resins and additives of the Brazilian HDPE geomembranes to guarantee products with long-term durability, avoiding losses in terms of human lives, environmental impacts, and financial costs.